2022
DOI: 10.3390/gels8070404
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Protein-Based Building Block (Albumin Methacryloyl) for Fabrication of a 3D In Vitro Cryogel Model

Abstract: Drug-induced liver injury (DILI) is a leading cause of attrition in drug development or withdrawal; current animal experiments and traditional 2D cell culture systems fail to precisely predict the liver toxicity of drug candidates. Hence, there is an urgent need for an alternative in vitro model that can mimic the liver microenvironments and accurately detect human-specific drug hepatotoxicity. Here, for the first time we propose the fabrication of an albumin methacryloyl cryogel platform inspired by the liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
1
7
0
Order By: Relevance
“…Therefore, CCK‐8 results and CLSM images demonstrated that HSAMA 4 hydrogels displayed good biocompatibility regardless of different HSAMA 4 concentrations, which is desired for tissue engineering applications. [ 106,107 ]…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, CCK‐8 results and CLSM images demonstrated that HSAMA 4 hydrogels displayed good biocompatibility regardless of different HSAMA 4 concentrations, which is desired for tissue engineering applications. [ 106,107 ]…”
Section: Resultsmentioning
confidence: 99%
“…Bovine serum albumin methacryloyl (BSAMA) cryogels were prepared according to a previous report [ 8 ]. Briefly, BSAMA powder was dissolved in PBS to form a clear BSAMA solution of 3%, 5%, and 10%.…”
Section: Methodsmentioning
confidence: 99%
“…Cryogels, as an example, differ from conventional hydrogels in that they display a 3D network of massive interconnected pores, highly crosslinked polymer walls, and excellent mechanical capabilities [ 6 ]. Cryogels can also be made for suturable intraoral grafts [ 7 ], and in vitro models that may replicate the microenvironments of the liver [ 8 ]. More importantly, cryogels support a somewhat strong resilience to autoclave (moist heat) sterilization, which is used as one of the terminal sterilization methods [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,102 Since specific ECM compounds can be very expensive, there is an option to produce scaffolds from more cost-efficient polymers and afterwards applying a bio-active coating to enhance cell adhesion and spreading. 103 Often used coating compounds in this regard include laminin, Fibronectin and collagen. [104][105][106] Alternative strategies described in literature include the application of decellularized native ECM (dECM) compounds used as biomaterial ink for scaffold fabrication/ printing or the decellularization and subsequent recellularization of natural liver tissue matrix.…”
Section: Reviewmentioning
confidence: 99%